The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/pmic.200500403
|View full text |Cite
|
Sign up to set email alerts
|

A mass spectrometric approach to identify arbuscular mycorrhiza-related proteins in root plasma membrane fractions

Abstract: One of the most important morphological changes occurring in arbuscular mycorrhizal (AM) roots takes place when the plant plasma membrane (PM) invaginates around the fungal arbuscular structures resulting in the periarbuscular membrane formation. To investigate whether AM symbiosis-specific proteins accumulate at this stage, two complementary MS approaches targeting the root PM from the model legume Medicago truncatula were designed. Membrane extracts were first enriched in PM using a discontinuous sucrose gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 61 publications
2
59
0
1
Order By: Relevance
“…In contrast, unlike SUT2, in PMenriched fractions we could not detect any peptide specific to MtPT4, the AM-inducible phosphate transporter that localizes on the branch domain of the periarbuscular membrane even though one might have expected the partitioning of the periarbuscular membrane with the plasmalemma because of the connectivity between the two. Because the cells containing arbuscules (and periarbuscular membranes) are diluted within total root tissues, it is possible that periarbuscular membrane proteins may fall below the detection limit (Valot et al 2006). We cannot exclude, however, that proteins belonging to the branch domain may not have been enriched to a similar extent as other PM proteins.…”
Section: Am-responsive Proteins As Related To Sugar/peptide Transportmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast, unlike SUT2, in PMenriched fractions we could not detect any peptide specific to MtPT4, the AM-inducible phosphate transporter that localizes on the branch domain of the periarbuscular membrane even though one might have expected the partitioning of the periarbuscular membrane with the plasmalemma because of the connectivity between the two. Because the cells containing arbuscules (and periarbuscular membranes) are diluted within total root tissues, it is possible that periarbuscular membrane proteins may fall below the detection limit (Valot et al 2006). We cannot exclude, however, that proteins belonging to the branch domain may not have been enriched to a similar extent as other PM proteins.…”
Section: Am-responsive Proteins As Related To Sugar/peptide Transportmentioning
confidence: 97%
“…After centrifugation at 16,000×g for 20 min, the supernatant was collected, filtered through two successive meshes (63 and 38 μm), and centrifuged at 96,000×g for 1 h. The microsomal pellet was resuspended in 10 mM Tris-MES, pH 7.3, 1 mM EDTA, 1 mM DTT, 1 mM PMSF, 10 μg/ml aprotinin, 10 μg/ml leupeptin, and 15% sucrose (w/w). PM enrichment from the microsomal fractions of AM and NM roots was initially performed using the sucrose gradient centrifugation protocol described in (Valot et al 2006). Microsomes (15% sucrose fraction) were loaded on a discontinuous sucrose gradient consisting of 3.5 ml of 38% (w/w) and 3 ml of 33% sucrose in 1 mM Tris-MES, pH 7.2, and 1 mM MgSO 4 .…”
Section: Root Microsome Extraction and Plasma Membrane Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In a comparison of membrane proteins from AM and non-AM M. truncatula roots, Valot et al (2006) identified two candidates present exclusively in mycorrhizal roots: a H + -ATPase, MtHA1, and a blue copper-binding protein, MtBcp1, which is predicted to be posttranslationally modified with a glycosylphosphatidylinositol (GPI) moiety. GPI anchors, which are added to secreted proteins in the ER after cleavage of a C-terminal peptide signal, result in localization of modified proteins to the extracellular leaflet of the plasma membrane (Eisenhaber et al, 2003).…”
mentioning
confidence: 99%